A comparison study of engineering students’ learning experience in face-to-face vs. synchronous modes - Akladios, Magdy; Retnanto, Albertus; Parsaei, Hamid R. (Intelektual Pustaka Media Utama, 2026)
While distance education offered many conveniences, it was not until the COVID-19 pandemic forced educators worldwide to utilize this option more that its full potential was realized. After the shutdowns, some institutions began to realize the benefits of continuing to offer some courses online to accommodate students who seek the conveniences of distance education. During the pandemic, Texas AM University campuses in College Station (CStat) and Qatar followed the recommended delivery methods implemented by the university in March 2020. The two undergraduate courses offered on these two campuses were the subject of empirical study at these universities. To identify the differences between the two campuses, this article will compare the findings of a survey that was given to students based on their academic performance and participation in both in-person and remote in-class (synchronous) learning. The survey used finite answers to simplify the comparison between the two sets of data, resulting in categorical-type data. The authors concluded that, regardless of location, if distance education is carried out consistently, the results should be similar after a chi-square comparison of the data revealed no significant differences between the two campuses.